Heat vulnerability in a hyper-arid coastal conurbation: downscaled LST and socio-spatial analysis - Sarricolea, Pablo (2025)
Heat vulnerability is a critical issue for cities under climate change, especially in socially precarious contexts and extreme climates such as deserts. The Iquique–Alto Hospicio conurbation in northern Chile represents a distinctive case study due to its marked altitudinal contrasts and rapid urban expansion. This research focuses on assessing the Surface Urban Heat Island (SUHI) at its peak expression, during summer nighttime conditions, in order to spatialize heat vulnerability. A multi-scalar workflow was applied, beginning with long-term multitemporal analysis of land surface temperature at moderate resolution (2002–2023) and extending to high-resolution downscaling for five recent years (2019–2023) using bilinear resampling combined with robust regression techniques. A heat vulnerability index was then developed through principal component analysis (four components, ∼74% variance explained), complemented by a spatial cluster analysis based on Anselin’s Local Moran’s I, which delineated statistically significant hot-spots in Iquique’s historic core and in recently formalized social-housing districts on the Alto Hospicio plateau, as well as cold-spots along the affluent coastal seafront. The results confirm the presence of a strong nocturnal summer SUHI, largely coinciding with the most densely populated areas characterized by low-rise housing and limited green space. The local climate zone Compact low-rise and lightweight built forms were identified as the most vulnerable to heat. The study concludes that effective strategies should promote less dense building typologies while incorporating urban infrastructures that act as climate refuges across the conurbation. More broadly, the approach offers a transferable template for climate-resilient planning in data-scarce, arid coastal cities worldwide.